KEBIJAKAN KRIMINAL (CRIMINAL POLICY) DALAM NEGARA HUKUM INDONESIA: UPAYA MENSEJAHTERAKAN AL-IMARAH: Jurnal Pemerintahan dan Politik Islam Vol. 2, No. 1, 2017 MASYARAKAT (SOCIAL WELFARE) - John Kenedi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
Abstract: The state of law as a translation of the word rechtsstaatsin terminology has a meaning parallel to the word Rule of Law, which guarantees Supremacy of Law or Supervisor Law, in countries in the world in general human rights are guaranteed by the Constitution or the Basic Law which is the source of the rights human rights, the same in the country of Indonesia as a State of Law. The provision that Indonesia is a Legal State is inseparable from the Preamble to the 1945 Constitution as the ideal of a state of law becoming a national ideal implemented in Article 1 Paragraph 3 of the Constitution of the Republic of Indonesia (third amendment). As the Indonesian national ideals that embrace the state of welfare law or a material law state that refers to Pancasila as the basic and the source of the law that is in the fifth principle of Pancasila which obliges the state to guarantee the realization of social justice for all Indonesian people. It is very clearly mandated in the second paragraph of the Preamble to the 1945 Constitution in the presence of words of justice and prosperity, then the third and fourth paragraph there is a word of God’s grace and Belief in God Almighty, related to religion and understood and understood as the needs of the people, both physical and spiritual. To create all it needs a law that is responsive through criminal policy (Criminal Policy).Keywords: State Law, Pancasila, Constitution and Criminal Policy